Analisis Kompetensi Pedagogik Guru Matematika SMP Negeri di Malang - Anik Kurniawati (Jurnal Kebijakan dan Pengembangan Pendidikan, 2013)
this study uses a descriptive qualitative research methods and quantitative methods. From the analysis said that there are still some pedagogical aspects need to be considered to be improved include: 1). Utilizing information and communications technology for the sake of learning held that earn points below the overall average that is equal to 3.71, 2). Facilitate the development of potential learners to actualize the potential of a variety of gain points below the overall average that is equal to 4.22, and 3). Reflective action to improve the quality of learning with an average of 4.14. While the professional competence of the average obtained by the calculation of the lack of data on aspects such as: 1). Develop professionalism in a sustainable manner by performing reflective acts with an average 4.04, and 2). Utilizing information and communication technologies to develop themselves obtained an average 3.64